PEMANFAATAN ABU BATUBARA SEBAGAI ZEOLIT YANG TERDEALUMINASI DALAM MENGADSORPSI FENOL - Agustinus Pata; Saibun Sitorus; Rahmat Gunawan (JURNAL KIMIA MULAWARMAN, 2014)
A research on the adsorption of phenol with zeolite adsorbent is formed from coal ash by hydrothermal process with the fusion method. In addition, the improvement in the ability of zeolite adsorbtion on the zeolite dealimination process is done. Phenol adsorption process is done through a batch shaker method with test parameters pH, contact time and adsorption capacity factor. The measurement results for the phenol optimum conditions were at pH 10 with a contact time of 30 minutes with the value of the phenol capacity of zeolite was 1,1853 mg/g were obtained using Langmuir isotherm adsorption equation.Keywords : Zeolite of coal ash, dealumination, adsorption, phenol.